First evidence of Halomicronema metazoicum (Cyanobacteria) free-living on Posidonia oceanica leaves. - Nadia Ruocco; Mirko Mutalipassi; Antonino Pollio; Susan Costantini; Maria Costantini; Valerio Zupo (PLoS ONE, 2018)
Cyanobacteria contribute to the ecology of various marine environments, also for their symbioses, since some of them are common hosts of sponges and ascidians. They are also emerging as an important source of novel bioactive secondary metabolites in pharmacological (as anticancer drugs) and biotechnological applications. In the present work we isolated a cyanobacteria in a free-living state from leaves of the seagrass Posidonia oceanica leaves. This newly collected strain was then cultivated under two laboratory conditions, and then characterized by combining morphological observation and molecular studies based on 16S rRNA gene sequences analysis. The strain showed 99% pairwise sequence identity with Halomicronema metazoicum ITAC101, never isolated before as a free-living organisms, but firstly described as an endosymbiont of the Mediterranean marine spongae Petrosia ficiformis, under the form of a filamentous strain. Further studies will investigate the actual role of this cyanobacterium in the leaf stratum of P. oceanica leaves, given its demonstrated ability to influence the vitality and the life cycle of other organisms. In fact, its newly demonstrated free-living stage, described in this study, indicate that Phormidium-like cyanobacteria could play important roles in the ecology of benthic and planktonic communities.